Co-application of sugarcane bagasse biochar, farmyard manure and mineral nitrogen improved growth indices of corn grown in alkaline calcareous soil. (27th May 2020) - Zafar-ul-Hye, Muhammad; Wasim, Muhammad Mubashir; Munir, Tariq Muhammad; Aon, Muhammad; Shaaban, Muhammad; Abbas, Mazhar; Hussain, Mubshar; Ahmad, Maqshoof
Abstract: Soil quality and crop productivity can be improved by the combined soil application of organic amendments and synthetic fertilizers. We evaluated the sole and combined effects of sugarcane-bagasse biochar (SBB), farmyard manure (FYM) and nitrogen (N) fertilizer on soil properties and corn yield traits. Three N fertilizer rates (0, 50 and 100% of recommended) were used with or without the organic amendments. We observed significant increases in soil nitrate-N (at vegetative and reproductive phases), ammonical-N and microbial-biomass-N contents in responses to a co-application of 0.5% SBB, 0.5% FYM and 100% N fertilizer ( p  ≤ 0.05). While the same co-application also resulted in the most significant soil organic carbon value, the maximum soil microbial biomass carbon was observed when 0.5% SBB and 0.5% FYM combination was applied along with 50% N fertilizer ( p  ≤ 0.05). Plant growth indices—shoot length and, fresh and dry weights of shoot and root were also recorded to be the highest where the same organic amendments were applied in addition to a 50% or 100% mineral N fertilizer ( p  ≤ 0.05). Combined application of the organic amendments effectively improved soil CEC compared to those in responses to individual applications of SBB and FYM ( p  ≤ 0.05). Conclusively, for increasing the corn yield and improving the soil quality, the co-application of 0.5% SBB and 0.5% FYM was more effective than any of the individual 1% applications; Additions of 50% and 100% mineral N to the organic combination were equally useful for increasing the grain yield.